Comparison of changes in amylase activity in the cotyledons of radish and lablab - Gaikwad, Sweta; Sharma, K (Journal of Phytology, 2012)
The food reserve of the seed may predominantly consist of fats, complex carbohydrates or storage proteins. To understand the chlorophyll content and various enzymatic activities taking place inside the seed i.e., in the cotyledons, it is very important and vital to analyze the degradation or synthesis of concerned products. However the work done so far with facts does open up some interesting possibilities of regulation of stored resources. The rate of degradation of starch is also slower than that of Radish. As we know that amylase activity is directly proportional to starch content. So this difference can be considered and justified. Thus it represents that the amylase is the major pathway of starch degradation in the axis and not that much significant in cotyledons of germinating seeds. The amylase activity is significant in cotyledons and is the best way to find out the parameters for the utilization of starch present.